Towards the contribution of follicular epithelium in the growing oocyte of Poekilocerus pictus (Orthoptera). A cytochemical study. - Saxena, R. C.; Jain, S.; Saxena, A.; Sahai, Y. N. (Contributions to Entomology = Beiträge zur Entomologie, 1988)
The follicular epithelium in the wrowing oocyte of P. picta plays a very significant role in the various synthetic activities. It also contributes towards the formation of "Chorion" or "egg envelop" in a mature oocyte. In addition to this, in P. picta during vitellogenesis stage, the epithelial cells grow in size and become binucleate and synthesise vitelline which is utilized by the oocyte according to ist physiological needs.